Friction Experiments for Dynamical Coefficient Measurement. (28th June 2011) - Arnoux, J. J.; Sutter, G.; List, G.; Molinari, A.
Abstract : An experimental study, including three experimental devices, is presented in order to investigate dry friction phenomena in a wide range of sliding speeds for the steel on steel contact. A ballistic setup, with an air gun launch, allows to estimate the friction coefficient between 20 m/s and 80 m/s. Tests are completed by an adaptation of the sensor on a hydraulic tensile machine (0.01 m/s to 3 m/s) and a pin-on-disk tribometer mounted on a CNC lathe (1 to 30 m/s). The interactions at the asperity scale are characterized by a white light interferometer surface analysis.